Robust Finite-Time H∞ Control for Impulsive Switched Nonlinear Systems with State Delay - Jian Guo (Mathematical Problems in Engineering, 2012)
This paper investigates robust finite-time H∞ control for a class of impulsive switched nonlinear systems with time-delay. Firstly, using piecewise Lyapunov function, sufficient conditions ensuring finite-time boundedness of the impulsive switched system are derived. Then, finite-time H∞ performance analysis for impulsive switched systems is developed, and a robust finite-time H∞ state feedback controller is proposed to guarantee that the resulting closed-loop system is finite-time bounded with H∞ disturbance attenuation. All the results are given in terms of linear matrix inequalities (LMIs). Finally, two numerical examples are provided to show the effectiveness of the proposed method.